Double Knockout of Akt2 and AMPK Predisposes Cardiac Aging without Affecting Lifespan: Role of Autophagy and Mitophagy - Wang, Shuyi (Biochim Biophys Acta Mol Basis Dis, 2018)
Increased age often leads to a gradual deterioration in cardiac geometry and contractile function although the precise mechanism remains elusive. Both Akt and AMPK play an essential role in the maintenance of cardiac homeostasis. This study examined the impact of ablation of Akt2 (the main cardiac isoform of Akt) and AMPKα2 on development of cardiac aging and the potential mechanisms involved with a focus on autophagy. Cardiac geometry, contractile, and intracellular Ca(2+) properties were evaluated in young (4-month-old) and old (12-month-old) wild-type (WT) and Akt2-AMPK double knockout mice using echocardiography, IonOptix® edge-detection and fura-2 techniques. Levels of autophagy and mitophagy were evaluated using western blot. Our results revealed that increased age (12 months) did not elicit any notable effects on cardiac geometry, contractile function, morphology, ultrastructure, autophagy and mitophagy, although Akt2-AMPK double knockout predisposed aging-related unfavorable changes in geometry (heart weight, LVESD, LVEDD, cross-sectional area and interstitial fibrosis), TEM ultrastructure, and function (fractional shortening, peak shortening, maximal velocity of shortening/relengthening, time-to-90% relengthening, intracellular Ca(2+) release and clearance rate). Double knockout of Akt2 and AMPK unmasked age-induced cardiac autophagy loss including decreased Atg5, Atg7, Beclin1, LC3BII-to-LC3BI ratio and increased p62. Double knockout of Akt2 and AMPK also unmasked age-related loss in mitophagy markers PTEN-induced putative kinase 1 (Pink1), Parkin, Bnip3, and FundC1, the mitochondrial biogenesis cofactor PGC-1α, and lysosomal biogenesis factor TFEB. In conclusion, our data indicate that Akt2-AMPK double ablation predisposes cardiac aging possibly related to compromised autophagy and mitophagy.